The role of unusual conscious experiences in mental illness : an exploration guided by process models of symptom formation and by a hierarchical theory of personal illness : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Barclay, John Craster (Massey University, 2001)
The relationship between non-clinical unusual conscious experiences and mental illness was explored cross-sectionally in 104 users of community mental health services. Morris (1997) organised unusual conscious experiences and psychiatric symptoms according to the cognitive process errors believed to underlie them, and highlighted the role in the formation of symptoms of difficulties in determining the intentions of the self and others. Foulds's (1976) hierarchical theory of personal illness predicted that progressively more serious layers of symptoms would be experienced, in addition to those already present, as the ability to discern intentionalily diminished. Participants completed the Delusions-Symptoms-States Inventory and the Conscious Experiences Questionnaire, and their primary clinicians provided Global Assessment of Functioning ratings. Foulds's hierarchical theory was found to be valid, and the frequency of unusual conscious experiences and deficits in determining intentionality increased the higher participants were placed on his hierarchy. Global functioning, although unrelated to position on the hierarchy or symptom related distress (findings attributed to the failure to assess negative symptoms) was weakly associated with the frequency of unusual conscious experiences. Cognitive process errors were positively correlated with each other, consistent with the errors occurring in the course of a single underlying process. Predicted associations were found between: delusions of persecution and difficulties in determining the intentions of others; hallucinations and the attribution of imagined percepts to external sources; grandiose delusions and the attribution of the actions of others to the self; conversion symptoms and the attribution of actions of the self to external sources; dissociative symptoms and the attribution of percepts with an external origin to the imagination; and delusions (of grandiosity, persecution, contrition, and passivity) and the attribution of events to an unseen power or force. Predicted associations were not found for passivity delusions or delusions of contrition. The implications for dimensional conceptions of mental illness are discussed, and research recommended to isolate the trait component of unusual conscious experiences. The utility of the cognitive process and intentionality findings are discussed in terms of generating hypotheses for future research, and guiding cognitive behaviour therapy and clinical management.
Keywords: Delusions; Hallucinations and illusions; Psychology, Pathological